(untitled) (Asian Journal of Medical and Biological Research, 2017)
The study was conducted to compare the growth and production performance of monosex and natural XY male tilapia of Oreochromis niloticus in Bismillah Agro production hatchery of Noakhali Sadar in Noakhali district, Bangladesh from September to November, 2014. The length, weight, average FCR value, Average SGR value, Daily weight gain, survival rate of fish were observed. Relationship between growth and physico-chemical parameter of water were also investigated for monosex and XY male tilapia. The finding of the study reveals that growth performance of naturally collected XY male tilapia is close to monosex tilapia. The SGR value was found better in monosex than XY male tilapia. . Among them, survival rate was found 95.06% in case of monosex whereas it was 93.67% for XY male. At the end of the experiment, average weight of monosex (179.5±1.32g) was found higher than XY male tilapia (167.8±1.10g). Average length of monosex (20.1±0.25cm) was also found higher than XY male tilapia (19.5±0.20 cm). Similarly, the average FCR value for monosex (1.39±0.185) was observed higher than XY male tilapia (1.71±0.233). Average SGR value for monosex (2.49±1.43) was also higher than the XY male tilapia (1.88±1.44). Daily weight gain of monosex (1.66±0.66g) was also experimental higher than XY male tilapia (1.53±0.611g) species. These findings will encourage the fish farmers to culture all XY male tilapia with minimal cost. Thus, the consumer and fish will be free from the risk of hormonal induction and farmers can able to maintain the sustainable production of tilapia and also their dependency on hatchery produced seed will be reduced. Asian J. Med. Biol. Res. September 2017, 3(3): 391-397